Chapter 15 Cloudwork Data Centre Labour and the Maintenance of Media Infrastructure - Taylor, A.R.E (Taylor & Francis, 2023)
Data centres underpin the architecture of cloud computing and form the operational backbone for digital communications and internet media. Yet, despite the rhetoric of the "on demand", "real-time" and "instant access" that characterises online consumption, it takes continuous work and upkeep to ensure that the online services provided by data centres remain constantly available, ready to be streamed or downloaded at the click of a button. This chapter follows the work of those tasked with operating and maintaining cloud infrastructure. It draws from fieldwork in a London-based data centre to explore the lived experiences of data centre labour that form the conditions of possibility for cloud media cultures and digital societies. Contributing to discussions of media infrastructures and digital labour, this chapter presents "maintenance" as an essential, but overlooked, form of media labour. If production, consumption and distribution have been understood as key media processes, less attention has been paid to maintenance, and to the people who operate and fix media infrastructure.